The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.7751/telopea20024002
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic revision of Araceae tribe Potheae (Pothos, Pothoidium and Pedicellarum) for Malesia, Australia and the tropical Western Pacific

Abstract: . A regional revision of the three genera comprising tribe Potheae (Araceae: Pothoideae) is presented, largely as a precursor to the account for Flora Malesiana; 46 species are recognized (Pothos 44, Pothoidium 1, Pedicellarum 1) of which three Pothos (P. laurifolius, P. oliganthus and P. volans) are newly described, one (P. longus) is treated as insufficiently known and two (P. sanderianus, P. nitens) are treated as doubtful. Pothos latifolius L. is excluded from Araceae [= Piper sp.]. The following new synon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Pothos barberianus belongs to subgenus Allopothos, the Barberianus group. It can be detected easily from its inflorescence pendent by the sharply reflexed peduncle, spathe strongly reflexed and spadix only just exceeding the greatly enlarged peduncle (Boyce and Hay 2001). Distribution and ecology.…”
Section: Homalomena Gillii Furtadomentioning
confidence: 99%
See 3 more Smart Citations
“…Pothos barberianus belongs to subgenus Allopothos, the Barberianus group. It can be detected easily from its inflorescence pendent by the sharply reflexed peduncle, spathe strongly reflexed and spadix only just exceeding the greatly enlarged peduncle (Boyce and Hay 2001). Distribution and ecology.…”
Section: Homalomena Gillii Furtadomentioning
confidence: 99%
“…This species is variable in size and the development of its inflorescence is closely linked to the vigour of the plant or even of an individual branch (300% size difference). Pothos beccarianus has two different types of inflorescences colour, yellow (common) and dark pink (rare) (Boyce and Hay 2001). Distribution and ecology.…”
Section: Homalomena Gillii Furtadomentioning
confidence: 99%
See 2 more Smart Citations
“…In other parts of India, it is found in Bihar, Goa, Karnataka, Kerala, Maharashtra and Tamil Nadu, Andaman and Nicobar Islands. [13][14][15][16][17][18][19][20][21][22][23][24] The earlier phytochemical studies on the current plant reported to contain both primary and secondary metabolites. The preliminary phytochemical screening reported some of the several secondary metabolites from the different parts of plant.…”
Section: Introductionmentioning
confidence: 99%